Conjunctival Exophytic Schneiderian-type Papillomas: A Rare Occurrence. Issue 5 (September 2021) - Charles, Norman C.; Stagner, Anna M.; Raju, Leela V.; Belinsky, Irina
Abstract : Conjunctival papillomas are common tumors that exhibit an exophytic growth pattern, comprised of multiple filiform fronds of squamous epithelium that contain fibrovascular cores. The inverted (endophytic) variety of papilloma, often termed "Schneiderian, " rarely occurs on the conjunctiva, with only 15 cases reported to date. Endophytic and exophytic papillomas are well described arising in the sinonasal Schneiderian epithelium where a low rate of malignant transformation may occur in the endophytic type; malignant transformation in exophytic sinonasal papillomas is exceedingly rare. The authors describe 2 cases of exophytic conjunctival papillomas with the morphology of a sinonasal or Schneiderian-type papilloma. Both were pink, sessile acquired growths in women in the sixth decade of life involving the inferior conjunctival fornix or nasal limbus. Nonkeratinizing squamous epithelium along with numerous goblet cells, intraepithelial mucinous cysts, and microabscesses were present. Immunohistochemistry showed reactivity for cytokeratin 7 and wild-type staining for p16 and p53, paralleling the findings in common conjunctival papillomas; both were also driven by low-risk human papillomavirus. Abstract : Two patients had sessile, exophytic papillomas excised from the lower fornix and bulbar conjunctiva which were found to be Schneiderian sinonasal-type papillomas, a unique occurrence in the conjunctiva.